Flow-Based Market Coupling Revised - Part II: Assessing Improved Price Zones in Central Western Europe - Björn Felten; Tim Felling; Paul Osinski; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance, 2019)
Part I of this two-part paper has presented flow-based market coupling (FBMC), the implicit congestion management method used to couple the CentralWestern European (CWE) electricity markets. It has also introduced a large-scale model framework for FBMC assessments, focusing on modeling the capacity allocation and market clearing processes. The paper at hand lays the focus on the newly developed redispatch model, thereby completing the description of the overall model framework. Furthermore, we provide a case study assessing improved price zone configurations (PZCs) for the extended CWE electricity system. Our case study is motivated by the ineffectiveness of managing congestion of intra-zonal lines described in Part I and by the possibility to reduce their relevance by improved PZCs. The importance of this study is substantiated by the controversial discussions on the currently-existing PZC. Thus, we assess the existing PZC and five novel PZCs determined by a cluster algorithm. Our results show that improved PZCs can reduce redispatch quantities and overall system costs significantly. Notably, we show that substantial improvements are possible when redesigning PZCs while maintaining a similar or slightly increased number of price zones. Moreover, under use of the theoretical considerations in Part I, we explain that increasing the number of price zones may not always increase welfare when using FBMC.
Keywords: D47; L51; Q40; Q41; Q48; 330; price zone; zonal pricing; flow-based market coupling; hierarchical clustering; redispatch